SOCIAL ECONOMIC VARIABLES INFLUENCE on HDI with DATA PANELS REGRESSION in KLASSEN CLUSTER at EAST JAVA PROVINCE - Sari, Indah Purnama; Subiyantoro, Heru; Saleh, Sugiyanto; Saleh, Sugiyanto (Journal of Economic Development, Environment and People, 2022)
This study analyzes the effect of socio-economic variables on HDI in East Java. Secondary data sources come from the Statistics Central Bureau of East Java Province. The research method used is cluster analysis and panel data regression. The sample quantity is 228 from panel data. The results showed that in a large panel of East Java gini ratio, population density, crime, and gender empowerment had a significant effect on HDI, while unemployment and economic growth had no significant effect on the HDI. In quadrant I, unemployment, economic growth, gini ratio, and population density have a significant effect on HDI, while crime and gender empowerment have no significant effect on the HDI. In quadrant IV, gini ratio, crime, and gender empowerment have a significant effect on HDI, while unemployment, economic growth and population density have no significant effect on the HDI. Simultaneously, all independent variables have a significant effect on the dependent variable HDI, and this applies to all panels.